Reduced serum magnesium is associated with the occurrence of diabetic macular edema in patients with diabetic retinopathy: A retrospective study - Xiang, Xiaoli; Ji, Zijia; Jiang, Tingwang; Huang, Zhengru; Yan, Jing (Frontiers in Medicine, 2022)
Serum magnesium levels have been reported to reflect the risk of diabetic retinopathy (DR); however, the effect of serum magnesium level on diabetic macular edema (DME) remains unclear. Here we investigated the association between serum magnesium levels and DME in patients with DR. Patients with DR were recruited between January 2020 and June 2021. A total of 519 patients with DR were included in this study. All patients underwent a standardized clinical ophthalmic examination by an experienced ophthalmologist, and an assay was conducted to determine serum magnesium concentration. The DME group had a higher proportion of insulin use and a higher level of serum ischemia-modified albumin and fasting plasma glucose compared to the non-DME group. Serum magnesium and calcium levels were lower in the DME group than in the non-DME group (P<0.05). Higher magnesium levels were negatively associated with DME after adjustment for relevant covariates. Compared to those in the lowest magnesium quartile, participants in the fourth quartile showed a significantly lower risk of DME after adjustment (odds ratio [OR], 0.294; 95% confidence interval, 0.153–0.566; P<0.0001). Taking into account the potentially different effects of serum magnesium on the development of DME in patients with DR based on age and insulin use, stratified analysis was performed by considering these factors. Among patients with DR using insulin aged 59–66 years, patients in the second, third, and fourth quartile of serum magnesium were less likely to develop DME than those in the lowest quartile of serum magnesium. (OR [95%CI], 0.094 [0.011–0.820], 0.070 [0.006–0.861], 0.039 [0.003–0.484]; P=0.032, 0.038, 0.012). Overall, a higher serum magnesium level was associated with a lower risk of DME in patients with DR. Furthermore, patients with DR who used insulin were more likely to develop DME. Long-term studies on oral magnesium supplements are needed to determine whether maintaining serum magnesium levels in a higher physiological range can reduce the risk of DME in patients with DR.